2017
DOI: 10.1080/1755876x.2017.1290863
|View full text |Cite
|
Sign up to set email alerts
|

Temperature and light patterns at four reefs along the Great Barrier Reef during the 2015–2016 austral summer: understanding patterns of observed coral bleaching

Abstract: Data from real-time sensor networks along the Great Barrier Reef (GBR) over the 2015-2016 austral summer showed that reef water temperatures exceeded empirical coral bleaching thresholds at a number of sites. Temperatures in the southern GBR were within historically normal limits with temperatures below the empirical bleaching threshold. The central GBR just reached the empirical bleaching threshold while, in the north, Lizard Island recorded four consecutive days above the bleaching threshold. Thursday Island… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
35
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(37 citation statements)
references
References 10 publications
2
35
0
Order By: Relevance
“…Ocean warming is considered to be one of the greatest threats to coral reefs (Baker et al, 2008;Hughes et al, 2018;Skirving et al, 2019). More than 90% of the heat energy accumulated in the Earth's climate system, largely a result of anthropogenic greenhouse gas (GHG) emissions, is stored in the ocean.…”
Section: Ocean Warmingmentioning
confidence: 99%
See 1 more Smart Citation
“…Ocean warming is considered to be one of the greatest threats to coral reefs (Baker et al, 2008;Hughes et al, 2018;Skirving et al, 2019). More than 90% of the heat energy accumulated in the Earth's climate system, largely a result of anthropogenic greenhouse gas (GHG) emissions, is stored in the ocean.…”
Section: Ocean Warmingmentioning
confidence: 99%
“…SST greater than ∼ 2 • C above the summertime maximum can result in coral bleaching over much shorter timescales, depending on coral tolerance to thermal and/or irradiance stress and on the magnitude and duration of exposure (Bainbridge, 2017). If stress levels subside quickly, corals may regain their zooxanthellae and recover, although surviving corals can have reduced growth, calcification and reproductive rates and a higher incidence of disease and competitive susceptibility (Baker et al, 2008;Ward et al, 2002;Chaves-Fonnegra et al, 2018). Recent work found an 89 % decline in larval recruitment during the 2018 spawning event in the GBR after consecutive mass bleaching events adversely affected populations of adult spawning corals (Hughes et al, 2019).…”
Section: Ocean Warmingmentioning
confidence: 99%
“…As many Scleractinian corals now reside in regions with SST close to their upper physiological limits, a 0.5º C rise in SST above the local summer maximum for a period of several weeks is sufficient to cause coral bleaching and mortality (Berkelmans, 2009). SST greater than ~2º C above the summertime maximum can result in coral bleaching over much shorter time-scales (Bainbridge, 2017). If stress levels subside quickly, corals may regain their zooxanthellae and recover, although surviving corals can have reduced growth, calcification and reproductive rates and a higher incidence of disease and competitive susceptibility (Baker et al, 2008;Ward et al, 2002;Chaves-Fonnegra et al, 2018).…”
Section: Ocean Warmingmentioning
confidence: 99%
“…Empirical evidence has demonstrated that DHW of 8° C-weeks reliably predicts mass coral bleaching and mortality (Liu et al, 2003). This is the most widely used measure for assessing and predicting coral bleaching events (Hughes et al, 2018;Bainbridge, 2017;Berkelmans, 2009 ;Skirving et al, 2019). The NOAA Coral Reef Watch is also producing a Light Stress Damage (LSD) measure which incorporates coral light stress as a contributor to coral bleaching, based on PAR anomalies (Skirving et al, 2017).…”
Section: Coral Reef Monitoringmentioning
confidence: 99%
See 1 more Smart Citation